A Study on Service Innovation Endeavours of Kashmiri Hotels - psgim, jcrm (Journal of Contemporary Research in Management (JCRM), 2023)
Innovation may be defined as the introduction of a new product or significantly improving upon an existing product or service or process or marketing strategy or organisational system or in peripheral relations. Service innovation at the organisation level may occur as an execution of novel or better business models, customer interfacing, evolving novel service products,developing novel standards, improved value proposal or enhancing competitive advantage by piercing into new markets or minimisation of cost of production by employing novel techniques. This descriptive research has collected data from 307 managerial personnel of Kashmiri hotels regarding their service innovation endeavours and results reveal that these hotels seem to accomplish the ultimate goal of business of satisfying customers through innovative services by utilising latest technology and service innovation has enhanced their efficiency. They have also agreed that service innovation has enabled them to offer better customised services suiting different customer needs in the market, leading them to acquiring better market share. The hotels are of the view that resources spent on innovating in the form of labour, time and finance is justified but they have expressed a slightly apprehensive opinion about their potentiality in introducing new and novel products. Furthermore, the study has revealed that A graded Kashmiri hotels, those located in the capital city of Srinagar, those in business for larger period of time and those operating in larger scale in terms of investment, turnover, number of rooms and employees engaged are innovating at larger scale while B graded Kashmiri hotels, those concentrating on both domestic and foreign customers and those and those operating at moderate scale in terms of number of rooms, employees engaged, investment and turnover are able to innovate to a reasonably moderate extent. This suggests the importance of large scale operations to innovate.